Triallel cross designs for comparing a set of test lines with a control line - Harun, Mohd; Varghese, Cini; Varghese, Eldho; Jaggi, Seema (The Indian Journal of Genetics and Plant Breeding, 2016)
Partial triallel cross (PTC) designs are suitable for developing crosses between inbred lines to study the genetic nature of quantitative traits in crops, which in turn help identify the strategy and methods of selection essential for breeding. PTCs are useful to compare test lines versus control line with more precision. In this paper, a method for constructing a class of PTC designs for comparing a set of test lines with a control line has been described. The proposed class of designs are variance balanced for estimating the contrasts pertaining to general combining ability effects of half as well as full parents. The suggested construction method doesn’t demand deep knowledge in statistics and therefore, the breeders can easily obtain small and efficient triallel cross plans for test lines vs. control line comparisons for their breeding trial.